Models for economic evaluation of multi-purpose apple harvest platform and software development - Zhang, Zhao; Zhang, Zhaohua; Wang, Xinmiao; Liu, Hu; Wang, Yuanjie; Wang, Weijie (International Journal of Agricultural and Biological Engineering, 2019)
An increasing number of U.S. apple growers are now interested in using harvest platforms to increase harvest productivity, expand labor pool, and alleviate tough working conditions. To maximize benefits, functions of thinning, pruning & training, and infield sorting have been or are to be incorporated into harvest platforms. Though growers are most concerned with economic benefits, few cost-benefit studies had been conducted on different platforms. In the meantime, economic analysis procedure is complex and each analysis is for one specific machine (not for general purposes). No software has been developed as a general and ready-to-use tool for growers and researchers for the platform economic analysis. In this study, platforms, both available on the marketplace and developed in lab as pilot trials, were reviewed. Costs and benefits models were then established, based on which multi-purpose apple harvest platform economic evaluation software (iMPAHP) was developed (capable of evaluating a wide variety of apple harvest platforms). A case study (machine cost of 100 000, accommodating 6 workers, processing apple incidence of 10% with 90% sort-out rate, and harvest, thinning, and pruning & training productivity increase by 40%, 50%, and 60%, respectively) based on iMPAHP demonstrated that infield sorting, harvest, thinning, and pruning and training accounted for 48.4%, 23.9%, 14.3%, and 13.4% of the total benefits, respectively. In the case that the platform was in all-four-purpose-application, the net present value (NPV) analysis of a 10-year investment showed a positive return of 60 547. However, without infield sorting function, the NPV resulted in a negative value, indicating a loss for the machine investment. Though incorporating the modular infield sorting system certainly increased the overall machine investment by 30 000, the benefits outweighed the costs. Keywords: multi-purpose apple harvest platform, economic evaluation, infield sorting, pruning, thinning, training DOI: 10.25165/j.ijabe.20191201.4360 Citation: Zhang Z, Zhang Z H, Wang X M, Liu H, Wang Y J, Wang W J. Models for economic evaluation of multi-purpose apple harvest platform and software development. Int J Agric & Biol Eng, 2019; 12(1): 74–83.